Comparative Analysis of the Financial Performance of Bank NTB Syariah Before and After Conversion - Abdul gani, Bhahari Abdul; Prasetyowati, Riris Aishah (Institut Agama Islam Negeri Madura, 2023)
Bank NTB Syariah officially converted on 28 September 2018. The conversion had a positive impact but did not guarantee to improve the bank's financial performance after the conversion. The purpose of the study was to identify differences in the performance of financial ratios of liquidity, solvency, and profitability of Bank NTB Syariah before and after the conversion. Secondary data used from the financial statements of Bank NTB Syariah for the period of the third quarter of 2014 to the second quarter of 2022. Wilcoxon Signed Rank Test was used to identify whether there is a significant difference in the performance of financial ratios of Bank NTB Syariah before and after the conversion. The results obtained show that the NPF, CAR, ROA, ROE, BOPO and NOM ratios have significant differences before and after the conversion, while the FDR and DER ratios show no significant difference.